12 steps to raw foods : how to end your dependency on cooked food - Boutenko, Victoria (Berkeley, Calif. : North Atlantic Books, 2007)
'A revised and expanded version of the original, this book illuminates the average person's multi-level attachment to cooked foods, explains how one can successfully transition to a raw food diet, and--relying on new scientific evidence--explains the health benefits of eating raw, living foods'--Provided by publisher
Includes bibliographical references (p. 257-258) and index
Keywords: Raw food diet; Raw foods